Proses Kreatif Penulisan Skenario Sobat Ambyar Mengadaptasi Budaya Lokal Musik Campursari - Adji, Titus Soepono; Suciati, Dica Mustika (Perkumpulan Program Studi Film dan Televisi Indonesia, 2024)
Sobat Ambyar is a film that adapts 2 things, namely Campursari songs created by Didi Kempot and the lives of Didi Kempot fans which are currently trending in 2021. This research aims to find out the creative process of scriptwriter Bagus Bramanti capturing these two phenomena which were then transferred to film medium. The research method used in this research is descriptive qualitative with data collection techniques through interviews and document study. The analysis process uses the stages of Graham Wallas' creative thinking with research results in the form of: preparation stage including basic provisions for writing scripts and story ideas, incubation stage in the form of research, illumination stage in the form of determining the plot and conducting Focus Group Discussions, then verification stage in the form of determining the genre, premise, ending & beginning, characters, setting and story scenario. In the screenwriting process, Bagus was assisted by two concepts in building drama, namely the Hero's Journey concept from Joseph Campbell and the Five Stages of Grief from Elisabeth Kubler Ross.